Validitas dan Kepraktisan Bahan Ajar IPAS Berbasis Multirepresentasi untuk Meningkatkan Keterampilan Kolaborasi Siswa Sekolah Dasar - Rahayu Budi Astuti; Supeno Supeno; Ary Purwantiningsih (Jurnal Pendidikan : Riset dan Konseptual, 2024)
Collaboration skills are one of the most important skills in 21st-century learning. However, in reality, collaboration skills in IPAS (Integrated Science and Social Studies) learning are still not optimal. This is because learning often only focuses on the teacher and does not provide deep learning experiences for students. Therefore, in this research, learning innovation is carried out in the form of developing teaching materials that develop collaboration skills and IPAS learning outcomes. The teaching materials that have been designed were then validated by three learning experts and tested on a limited basis on fourth-grade students of SDN 1 Bendogerit, Blitar City, East Java. However, before the teaching materials were tested, they were validated by experts and practitioners, showing validity criteria with content validity of 3.59 and construct validity of 3.71. The validators suggested improving the print quality and illustrations. In addition, the cloze test results showed practicality with a good level of readability, with 4 out of 6 students considering the test easy. The average percentage of correct answers reached 65%, with variations of 40-90%. Although no students found the test difficult, special attention is needed for students in the medium category. Thus, it can be concluded that the developed teaching materials are valid and practical, referring to the validation results and the cloze test obtained.